The use of methylene blue in adult patients with septic shock: a systematic review and meta-analysis - Ka Ting Ng; Pei En Kwok; Wei En Lim; Wan Yi Teoh; Mohd Shahnaz Hasan; Mohd Fitry Zainal Abidin (Brazilian Journal of Anesthesiology)
Objectives: Methylene blue exerts its vasopressor properties by inhibiting nitric oxide-mediated vasodilation. Recent studies have advocated the use of methylene blue as a rescue therapy for patients with septic shock. The primary aim was to investigate the effect of methylene blue on the mean arterial pressure among adult patients with septic shock. Methods: Databases of MEDLINE, EMBASE, and CENTRAL were searched from their inception date until October 2023. Randomized Clinical Trials (RCT) comparing methylene blue and placebo in adults with septic shock were included. Results: Our systematic review included 5 studies (n = 257) for data analysis. As compared to the placebo, our pooled analysis showed that methylene blue significantly increased mean arterial pressure (MD: 1.34 mmHg, 95% CI 0.15 to 2.53, p = 0.03, level of evidence: very low). Patients who were given methylene blue were associated with statistically lower mortality rate (OR = 0.49, 95% CI 0.27 to 0.88, p = 0.02, level of evidence: low), reduced serum lactate levels (MD: -0.76 mmoL.L-1, 95% CI -1.22 to -0.31, p = 0.0009, level of evidence: low), reduced length of hospital stay (MD: -1.94 days, 95% CI -3.79 to -0.08, p = 0.04, level of evidence: low), and increased PaO2/FiO2 (MD: 34.78, 95% CI 8.94 to 60.61, p = 0.008, level of evidence: low). Conclusions: This meta-analysis demonstrated that methylene blue administration was associated with an increased in mean arterial pressure and PaO2/FiO2 ratio, along with a reduction in mortality rates, serum lactate levels, and length of hospital stay. However, substantial degree of heterogeneity and inadequate number of studies with low level of evidence warrant future adequately powered RCTs to affirm our results.